Développement d'un film alimentaire bioactif et intelligent à base d'amidon et de la curcumine - AMURI SHERALY, ZUBERI; MERABET, NOUR ELYAKINE (My University, 2023)
Active and intelligent films with antioxidant, antimicrobial and pH–responsive properties were developed by adding curcumin (Cur) and/or polyvinyl alcohol (PVA) into corn starch (CS) matrix. Functional properties of CS, CS/PVA, CS–Cur, and CS/PVA–Cur films were compared. Results showed the addition of Cur effectively changed the films colors when they are exposed to different pH mediums. By comparing different films, CS–Cur and CS/PVA–Cur films presented the stronger microbial growth inhibition as well as the potent free radical scavenging ability than CS and CS/PVA films. Notably, CS/PVA–Cur film packaging effectively demonstrated the monitoring of veal freshness and could be used as novel multifunctional packaging food industry.
Keywords: Active packaging; Intelligent packaging; Starch; Polyvinyl alcohol; Curcumin